2021
DOI: 10.1186/s12978-021-01195-8
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and its factors of post abortion modern contraceptive in Ethiopia: a systematic review and meta-analysis

Abstract: Background Providing post-abortion care service is a widely accepted to reduce maternal morbidity and mortality by promoting, preventing and treating maternal and neonatal health, identifying the utilization and its factor of post abortion contraceptive is crucial. Therefore we tried to review post abortion contraceptive utilization and its factors in Ethiopia. Methods A review was performed by using the Preferred Reporting Items for Systematic Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The un-counselled group might have not chosen a PAFP method due to lack of information about PAFP whilst the comprehensively counselled group might have been bored with a lengthy discussion which made them lose track of the core message in the process. Similarly in Ethiopia, two meta-analysis studies involving 11 studies and 16 studies found out that counselled women had ve and three times higher chances respectively of utilizing PAFP than those who did not receive any counselling (Beyene et al, 2021;Cherie et al, 2022). Women who were counselled might have had a raised awareness about PAFP.…”
Section: Socio-demographics and Reproductive Determinants Of Post-abo...mentioning
confidence: 98%
“…The un-counselled group might have not chosen a PAFP method due to lack of information about PAFP whilst the comprehensively counselled group might have been bored with a lengthy discussion which made them lose track of the core message in the process. Similarly in Ethiopia, two meta-analysis studies involving 11 studies and 16 studies found out that counselled women had ve and three times higher chances respectively of utilizing PAFP than those who did not receive any counselling (Beyene et al, 2021;Cherie et al, 2022). Women who were counselled might have had a raised awareness about PAFP.…”
Section: Socio-demographics and Reproductive Determinants Of Post-abo...mentioning
confidence: 98%
“…We found that several existing reviews focused on the determinants of contraceptive use in LMIC [9][10][11]. These reviews focused on a specific subgroup of contraceptive users, such as those with HIV or those with diabetes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%